Fostering knowledge sharing and capacity building of tricot best practices through the 1000FARMS community of practice - 1000FARMS Platform (2025)
This poster summarizes the development of the 1000FARMS Community of Practice to support knowledge exchange and capacity strengthening among tricot users. It addresses the challenges of dispersed resources and limited peer-to-peer learning, and presents solutions such as training events, webinars, and a future reference book. The initiative seeks to consolidate and amplify tricot best practices across regions and user groups